Methotrexate in Crohn's disease: a new face for an old drug?. (2nd October 2016) - Cesarini, Monica; Festa, Stefano; Papi, Claudio
ABSTRACT: Introduction : Methotrexate is commonly used in rheumatoid arthritis but randomised controlled trials demonstrated its efficacy also in Crohn's disease. Methotrexate, although marginally used in clinical practice, is considered an appropriate immunomodulator particularly in patients refractory or intolerant to thiopurines. Areas covered : A literature search using 'methotrexate', 'Crohn's disease' and 'Inflammatory Bowel Disease' as key words, identified randomised controlled trials, meta-analyses and observational studies. The aim of this review is to summarise and critically discuss the available evidence concerning the efficacy and safety of methotrexate in the treatment of Crohn's disease. Expert commentary : Methotrexate is effective in inducing and maintaining remission in steroid-dependent CD at a dose of 25 mg/week and 15 mg/week, respectively. Data from observational studies suggest that methotrexate may be as efficacious as thiopurines with a similar safety profile. In specific clinical settings, (patients with a history of malignancy or young Epstein-Barr Virus–seronegative patients), methotrexate compete favourably with thiopurines.